Cross cultural logistics and supply chain management towards organizational effectiveness within the asean/Thai automotive industries: A sem analysis - Dansomboon, Suwaj; Phimonsathienand, Thepparat; Fongsuwan, Wanno (My University, 2016)
As a manufacturing, logistics and supply chain hub within ASEAN (Association of Southeast Asian Nations), Thailand holds the 12th spot in global vehicle production for an estimated 2,355 Thai and multinational automotive industry enterprises. Within the Association of Southeast Asian Nations, Thailand ranks number one in automotive production contributing $US11.4 billion to the Thai economy and 12 percent to Thailand's GDP (Gross Domestic Product), with the automotive industry being Thailand's leading export sector. However, the automotive companies envisage the difficulty of cultural diversity to manage and coordinate. Therefore, cultural values from the milieu are inducted into the workplace and have a strong impact on both individual behavior and organizational effectiveness and must be direction at all levels for cross-cultural, organizational effectiveness to be achieved. It also became evident that natural disasters are frequent and highly disruptive to the global automotive supply chain and paces must be taken to countervailing the notable and continuing loss to economic growth and organizational effectiveness to both sector units and the global industry. The implementation of strategically placed, environmentally 'habituated', automotive parts logistics cache might be one solution to the problem. Given the crucial importance of this sector to the economy of the region and the global supply chain, the researchers surveyed 220 managers using a 7-point Likert scale questionnaire within the multinational industrial clusters of Thailand's 'Detroit of Asia' Eastern Seaboard region. Using Structural Equation Modelling to test the 11 variables on Logistics Management, Supply Chain Management and Organizational Effectiveness in a cross-cultural context, it was determined that collaboration within the supply chain and the exchange of information can reduce uncertainty, with trust being a key ingredient to a JV's success. Communication (0.836), trust (0.834) and collaboration (0.824) were ranked as significant components of cross-cultural Supply Chain Management effectiveness. The research also confirmed that the hypothesized difficulty from cultural diversity is difficult to manage and to coordinate. Analysis also confirmed the ongoing and significant problems to the global automotive supply chain by natural disasters and the consequential economic losses.
Keywords: AEC; automobiles; collaboration; communications; human resources; natural disasters; SEM; trus; vehicles